Edukasi Literasi Keuangan, Investasi, Financial Technology, dan Pengelolaan Keuangan Pribadi - Utami, Novia; Kusumahadi, Teresia Angelia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
In the current digital era, financial literacy is crucial to support wise financial management and prevent the risk of fraud, especially among the younger generation. This article discusses the need for financial literacy, especially among high school students, to help them manage personal finances, understand investments, and become familiar with financial technology (fintech). Cases of fraud, such as several students caught in online loans, emphasize the importance of understanding financial literacy in financial decisions. From the evaluation results of the financial literacy workshop conducted at SoliDEO Christian High School, this activity positively impacted students' understanding of investment, financial literacy, and financial technology. A significant increase in students' interest scores regarding these various aspects was seen through surveys before and after the workshop. The highest increase occurred in understanding investment instruments, followed by the urgency of recognizing red flags when investing, financial literacy, use of financial technology, and investing in general. Even though there has been an increase, the importance scores for understanding and measuring investment profits and risks, managing personal finances, and making a priority scale for spending funds tend to be stable.